Student Perception Of Using Storytelling and The Advantages In Speaking Class at the Seventh Grade of Al-Ma’soem Junior High School - Ramadani, Rina (Jurnal Dimamu, 2025)
Background of this research is due to the application of storytelling methods in language teaching, teachers can make learning more interesting and effective, allowing students to understand spoken language better. The aim of this research is to find students' perceptions regarding the use of storytelling in learning speaking in class and to find the advantages of using storytelling in learning speaking in class. This research uses a qualitative descriptive method with questionnaire and interview instruments. Questionnaires to answer the results of student perceptions regarding the use of storytelling methods in student learning in class and interviews to answer the advantages of using storytelling in learning speaking in class. This research was conducted at one of the private schools in Bandung, namely Al Ma'soem Middle School, specifically in class VII E. The subjects were the English teacher and students in the class.This research shows that using storytelling is very fun and students really like this method, whether they like English or those who don't like English. From these results, there are several benefits from using the storytelling method, namely enriching vocabulary, making learning speaking fun, improving pronunciation, training students to speak up.